The influence of visionary leadership and job satisfaction on the performance of employees of the Central Statistics Agency of Deli Serdang Regency - Retno Prihandayani; Anggia Sari Lubis (Journal Of Management Analytical and Solution (JoMAS), 2024)
This study aims to determine and analyze the influence of visionary leadership and job satisfaction on employee performance at the central statistical agency for Deli Serdang district. The sampling technique used saturated sampling technique, amounting to 40 respondents. Methods of data collection using a questionnaire. The results of multiple linear regression analysis obtained the equation Y = 12.107 + 0.495X1 + 0.428X2. In the partial test (t test) the Visionary Leadership variable has a positive and significant effect on Employee Performance with a t calculated value of 5.374 > t table 1.986 and a significant value of 0.000 <0.05 and the Job Satisfaction variable has a positive and significant effect on Employee Performance with a t calculated value of 2.570 > t table 1.986 and a significant value of 0.000 <0.05. Simultaneous significant test results (Test F) Visionary Leadership and Job Satisfaction variables simultaneously or together have a positive and significant effect on Employee Performance with an F count of 142.714 > F table of 3.10 and a significant value of 0.000 <0.05. test results The coefficient of determination ã€–(Rã€—^2) obtained an R Square value of 0.885 meaning that the Employee Performance variable can be explained by 88.5% by the Visionary Leadership and Job Satisfaction variables while the remaining 11.5% is explained by other variables not included in the study This.